2008
DOI: 10.3238/arztebl.2008.0397
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Quality of Life in Patients With Amyotrophic Lateral Sclerosis

Abstract: The rationale for not providing life-sustaining treatment to severely disabled patients is that a poor quality of life is expected after such treatment. Our studies have shown, however, that ALS patients can experience a satisfactory quality of life without depressive manifestations even if they are severely physically impaired, including in the terminal phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
96
2
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(121 citation statements)
references
References 40 publications
14
96
2
5
Order By: Relevance
“…This also applies if the persons suffering from neuromuscular diseases and having a higher degree of education degree of education report on the general overall quality of life. In contrast to the findings of Robbins et al (2001), Lulé et al (2008), and Raspe (1990), the assessment of overall quality of life within the scope of this survey of persons having a neuromuscular disease is lower than in a comparison sample with persons not suffering from neuromuscular or other chronic diseases.…”
Section: Resultscontrasting
confidence: 92%
See 2 more Smart Citations
“…This also applies if the persons suffering from neuromuscular diseases and having a higher degree of education degree of education report on the general overall quality of life. In contrast to the findings of Robbins et al (2001), Lulé et al (2008), and Raspe (1990), the assessment of overall quality of life within the scope of this survey of persons having a neuromuscular disease is lower than in a comparison sample with persons not suffering from neuromuscular or other chronic diseases.…”
Section: Resultscontrasting
confidence: 92%
“…Robbins et al (2001) showed that the assessment of the quality of life of patients with ALS does not primarily depend on the physical state of health. In a study by Lulé et al (2008), the average subjective quality of life of ALS patients was 66-72 % and thus in an area that is comparable with healthy control persons. Similar results regarding the fact that many chronically ill people feel "quite well actually" are reported by Raspe (1990).…”
Section: Quality Of Life Within the Framework Of Neuromuscular Diseasesmentioning
confidence: 93%
See 1 more Smart Citation
“…Thus, the fact that impaired functional outcome is more common among patients older than 60 years would suggest lower retrospective consent. On the other hand, evidence shows that patients can accommodate to even severe neurologic deficits over the longer term, especially when they already have experience with functional impairment [17] . Therefore, it is possible that older patients could exhibit higher acceptance of functional deficits.…”
mentioning
confidence: 99%
“…The ALSAQ40 is a measure of quality of life in ALS (24). While quality of life is undoubtedly important, it is not tightly linked with physical disability in ALS (25) and can even be influenced by psychiatric interventions (26); thus the ALSAQ40 is not an acceptable primary measure of ALS disease progression. Changes in this quality of life scale cannot be extrapolated to changes in life expectancy.…”
Section: Data In Palsmentioning
confidence: 99%